Electrodynamics open up the world of metamaterials - Даулетбекова , A. К.; Шварц , К.; Сорокин , М. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
Электродинамика открывает мир метаматериалов